Idaho State Building (Pacific Novelty Co.)
On verso: Idaho was the first of the States to complete and dedicate its building. The handsome structure stands on the shores of the bay and contains a motion picture theater for display of a truly wonderful selection of reels, showing the industries and resources of the State, also executive offices and rooms for the reception of visitors.